2006
DOI: 10.1175/mwr3066.1
|View full text |Cite
|
Sign up to set email alerts
|

The “Triple Point” on 24 May 2002 during IHOP. Part I: Airborne Doppler and LASE Analyses of the Frontal Boundaries and Convection Initiation

Abstract: An analysis of the initiation of deep convection near the triple point between a cold front and dryline is presented. High-spatial-resolution Doppler wind syntheses combined with vertical cross sections of mixing ratio (q) and aerosol scattering ratio retrieved from a lidar flying over the triple point provide an unprecedented view of the initiation process. The Doppler wind synthesis revealed variability along the dryline similar to the precipitation core/gap structure documented for oceanic cold fronts. Vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 48 publications
(64 reference statements)
0
24
0
Order By: Relevance
“…However, any finelines that originated from thunderstorm outflow were removed, as were any that may have been outflow related but whose origin was difficult to discern. Finelines often appear on radar plan position indicator displays as a thin line of relatively higher reflectivity within regions of strong convergent boundary layer flow (Wilson and Schreiber 1986;Wilson et al 1994) and have been used in a number of previous studies to help identify the location and movement of drylines (Atkins et al 1998;Murphey et al 2006;Wakimoto et al 2006;Weiss et al 2006;Miao and Geerts 2007;Geerts 2008;Campbell et al 2014). Drylines may not always be accompanied by a fineline, especially if occurring in the presence of weak convergent (or divergent) flow or when passive boundary layer scatterers (such as insects) are not abundant.…”
Section: B Selection Of Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, any finelines that originated from thunderstorm outflow were removed, as were any that may have been outflow related but whose origin was difficult to discern. Finelines often appear on radar plan position indicator displays as a thin line of relatively higher reflectivity within regions of strong convergent boundary layer flow (Wilson and Schreiber 1986;Wilson et al 1994) and have been used in a number of previous studies to help identify the location and movement of drylines (Atkins et al 1998;Murphey et al 2006;Wakimoto et al 2006;Weiss et al 2006;Miao and Geerts 2007;Geerts 2008;Campbell et al 2014). Drylines may not always be accompanied by a fineline, especially if occurring in the presence of weak convergent (or divergent) flow or when passive boundary layer scatterers (such as insects) are not abundant.…”
Section: B Selection Of Casesmentioning
confidence: 99%
“…While the latter has led some researchers to conclude that drylines frequently behave as density currents (Ziegler and Hane 1993;Atkins et al 1998;Geerts 2008), others have shown evidence that suggests this is not always the case (e.g., Crawford and Bluestein 1997). Moist convection, including thunderstorm formation, frequently occurs along drylines, although the mechanisms responsible for initiating such convection remain poorly understood and have been the focus of much research in recent decades (Koch and McCarthy 1982;Ziegler et al 1997;Wakimoto and Murphey 2009). Often, these storms become severe as they may attain supercellular characteristics as a result of the highly sheared environment common near drylines (Weiss et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, dryline-induced vertical circulation patterns can effectively erode these capping inversions allowing convection initiation to occur. Several mechanisms for convection initiation along the dryline have been observed, including localized forcing from circulations associated with horizontal convective rolls, as well as gravity waves propagating eastward on top of the subtropical boundary layer (Ziegler et al 1997;Ziegler and Rasmussen 1998;Wakimoto et al 2006;Xue and Martin 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the interaction between convective cells and other mesoscale circulations, such as sea breeze (Atkins et al, 1995;Dailey and Fovell, 1999;Ogawa et al, 2003), river breeze (Rao et al, 1999) and dryline (Atkins et al, 1998;Peckham et al, 2004;Wakimoto et al, 2006;Xue and Martin, 2006) circulations, have emphasized that convective cells significantly modulate the frontal structures of the sea breeze, river breeze and dryline, thus leading to the horizontal variability of the frontal structures. For example, horizontal convective rolls create vertical velocity maxima at the points where they intersect with the dryline, which plays a key role for initiating clouds at these intersection points (Atkins et al, 1998).…”
Section: Introductionmentioning
confidence: 99%